Dominance of Wildfires Impact on Air Quality Exceedances During the 2020 Record‐Breaking Wildfire Season in the United States. Issue 21 (2nd November 2021) - Li, Yunyao; Tong, Daniel; Ma, Siqi; Zhang, Xiaoyang; Kondragunta, Shobha; Li, Fangjun; Saylor, Rick
Abstract: The western United States experienced a record‐breaking wildfire season in 2020. This study quantifies the contribution of wildfire emissions to the exceedances of health‐based National Ambient Air Quality Standard (NAAQS) for fine particles (PM2.5 ) by comparing two CMAQ simulations, with and without wildfire emissions. During August to October 2020, western wildfires contributed 23% of surface PM2.5 in the contiguous US (CONUS), with a larger contribution in Pacific Coast (43%) and Mountain Region (42%). Consequently, wildfires were the primary contributor to the 3, 720 observed exceedances. The wildfire influence peaked on September 14th, 2020, when 273 exceedances were recorded and wildfire emissions contributed 41%, 81%, and 72% to surface PM2.5 concentrations in the CONUS, Pacific Coast, and Mountain Region, respectively. Our finding highlights the predominating influence of wildfires on air quality, and potentially human health, that is expected to grow with increasing fire activities, while anthropogenic emissions decrease. Plain Language Summary: In the summer of 2020, the western United States experienced a record‐breaking number of wildfires. We looked into the effects of these wildfires on air quality, through the lens of the exceedances of health‐based National Ambient Air Quality Standards (NAAQS) for fine particles (PM2.5 ), which are associated with the bulk of health risks posed by air pollution. We found that in 2020, the western wildfires contributed 23% of surface PM2.5 pollution during August to October in the contiguous United States. The contribution is much bigger in the Pacific Coast (43%) and the Mountain Region (42%). Consequently, the wildfires were the primary contributor to the 3, 720 exceedances of PM2.5 NAAQS. Our finding highlights the dominating influence of wildfire emissions on air quality and potentially on human health. Key Points: Wildfire emissions contribute 23% of surface PM2.5 concentration in the contiguous United States during the summer of 2020 Wildfires were the primary contributor to the 3, 720 exceedances of National Ambient Air Quality Standard for PM2.5 during the 2020 summer Our finding highlights the predominating influence of wildfires on air quality during the 2020 wildfire season